Rare bird documentation form for Glaucous Gull at Lake Manawa in 1978 - Kovanda, James, Jr.et al; Kovanda, Sandraet al (1978)
Rare bird documentation form for a Glaucous Gull at Lake Manawa in Pottawattamie County, IA on December 6 and 7, 1978. Epson - sheet feed